Case report: A novel STXBP1 splice variant and the landscape of splicing-involved STXBP1-related disorders - Wang, Haiping; Chen, Xiuli; Liu, Zhanli; Chen, Chen; Liu, Xin; Huang, Mingwei; Zhou, Zhuying (Frontiers in Neurology, 2023)
STXBP1 variants are one of the most common genetic causes of neurodevelopmental disorders and epilepsy, wherein STXBP1-related disorders are characterized by neurodevelopmental abnormalities in 95% and seizures in 89% of affected patients. However, the spectrums of both genotype and phenotype are quite wide and diverse, with a high baseline variability even for recurrent STXBP1 variants. So far, no clear genotype-phenotype correlations have been established and multiple disease mechanisms have been proposed for STXBP1-related disorders. Without an ascertained disease cause for many cases of STXBP1 variants, it is challenging to manage this disease in an effective manner and current symptom-based treatments are focused on seizure control only, which have minimal impact on global development. A novel STXBP1 canonical splice variant, NM_001032221.4:c.578+2T>C, was reported in this study, together with a detailed documentation of disease manifestations and treatment management. Further RNA expression analysis revealed abnormal intron retention and possible resulted production of truncated STXBP1 proteins as a likely pathogenic mechanism. More importantly, the landscape of previously understudied STXBP1 splice variants and functional investigations was assessed for the first time, to provide a context for discussion of the complicated genotype-phenotype relationship of STXBP1-related disorders. Future cases of this disorder and deeper mechanism-based understanding of its pathogenic cause are required for precision medicine and better disease management.